As características do coronelismo e sua prática na política brasileira - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2014)
This article presents a study of the “coronelismo” phenomenon in Brazil. Makes an analysis of its historical process. Later comes on the relevant issues on their updates during the political history in Brazil and shows how such practices keep on. The compromise between the political entities and the submission of the population still exists, as well as the living conditions of the population are no good, contributing to the maintenance of “coronelismo”.
Keywords: Coronelismo - Política; Coronelismo - Brasil; Coronelismo eletrônico; Clientelismo; CNPQ::CIENCIAS SOCIAIS APLICADAS